THE IMPACTS OF POLITICAL AND SOCIAL CONTEXT ON SHAPING DEMOCRATIC CULTURE VIA TEACHING HUMAN RIGHTS IN HIGHER EDUCATION OF MYANMAR - May Thida Aung (Asia-Pacific Journal of Elections and Democracy, 2022)
A number of reforms followed Myanmar’s political transformation in 2011, including the introduction of human rights courses in the higher education system in the 2016/17 academic year. This study argues that the legacy of prolonged military regimes and the social context limits the practical teaching of human rights in the classroom. This study evaluates how university lecturers taught human rights between 2015-2020 and how it influenced the contents of the subject and the way of delivering human rights knowledge even under the democratically elected government. The study finds that many lecturers were hesitant to engage in a deep discussion on politically and socially sensitive issues because academic freedom is still relatively fragile, even though the National Education Law 2014 and National Education Strategic Plan (2016~2021) guarantee academic freedom. Furthermore, the study-centered learning approach was challenging due to the unfamiliarity of the methods by both students and lecturers. The study suggests improving the quality of human rights teaching to support the sustainability of democratic culture in Myanmar.